DEVELOPING CREATIVITY IN VOCATIONAL HIGH SCHOOL (SMK) CULINARY ARTS STUDENTS TO ENHANCE PRODUCT INNOVATION: A SCOPING REVIEW - Rini Purwaningrum; Abdul Muhid (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
Rapid technological advancement and shifts in learning paradigms require vocational education, particularly in the culinary field, to continuously innovate in order to enhance students’ creativity and product development skills. Creativity and innovation are essential competencies for Vocational High School (SMK) students to remain competitive in the context of Industry 4.0. This study employs a systematic literature review to examine learning strategies that effectively promote creativity and culinary product innovation in SMK. A total of eight peer-reviewed scientific articles were analyzed, focusing on the implementation of Project-Based Learning (PjBL), the integration of Virtual Reality (VR) and gamification, and contextual learning approaches based on local culture. The findings indicate that PjBL contributes significantly to the development of students’ creative thinking, collaboration, and problem-solving abilities through authentic project experiences. Furthermore, the use of VR and gamification enhances learning motivation, student engagement, and reflective thinking during the learning process. In addition, the incorporation of local cultural elements strengthens the contextual relevance and social value of culinary products, allowing students to connect learning outcomes with real-world and cultural contexts. Collectively, these approaches create an effective learning environment that supports meaningful, technology-enhanced, and authentic culinary education. The practical implication of this study highlights the importance for SMK teachers to design integrated learning environments that combine project-based activities, digital simulations, and gamified elements as a sustainable creative learning ecosystem aligned with the demands of Industry 4.0.